An agent-based behavioral model of technology consumers in a dynamic social network (2017)
ABSTRACT: This article describes the design of a model to identify the relevant factors in the decision-making process of consumers that adopt technology within a dynamic social network. The proposed model includes specific theories and tools from the psychology of consumer behavior, social networks, and complex dynamical systems. The model has been developed to work with the mobile smartphone market and was able to describe trends similar to those described in the real world market.